Maine’s Homeless Families: An Interview with Helen Hemminger - Hemminger, Helen (Maine Policy Review, 1999)
Since 1991 Helen Hemminger has been director of The Tedford Shelter, a homeless shelter serving adults and families in the Brunswick, Maine area. In this interview, Hemminger provides a first- hand account of Maine’s changing homeless population. The good news, she reports, is that the percentage of people with mental illnesses staying at the shelter has gone down. The bad news is that since 1994 the shelter has experienced a steady increase in the number of homeless families. As Hemminger notes, there are more Maine families today working very hard to make ends meet. Living on a precarious edge, one setback—like temporary unemployment or a health problem—can put them over the edge and, literally, on the streets. Hemminger provides her thoughts on how best to help this growing, vulnerable population.